Brand Authenticity and Perceived Service Value as Determining Factors of Consumer Loyalty in Culinary Business of Cafes and Restaurants in Makassar - Gianina Evangeline Kapang; Adeline Aldora Chandra; Audrey Inggrid Larasati Djoemani; Asriah Syam (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Kristen Indonesia Paulus, 2026)
Introduction: The culinary business in Makassar has grown significantly, with numerous cafes and restaurants emerging across the city. However, many newly established culinary businesses fail to sustain operations in the long term. Long-standing establishments tend to retain loyal customers and maintain business continuity. This aims to investigate the factors influencing customer loyalty by focusing on two independent variables brand authenticity and perceived service value with brand attachment serving as a mediating variable. Methods: A quantitative research method was applied, using a structured questionnaire distributed online to customers who have visited cafes or restaurants in Makassar that have operated for more than ten years. The minimum sample size was determined using Lemeshow’s formula, with at least 96 respondents targeted. Data analysis was conducted using Structural Equation Modeling with Partial Least Squares (SEM-PLS) via SmartPLS software. Results: Preliminary expectations based on the conceptual framework suggest that brand authenticity and perceived service value both have a significant direct and indirect effect (through brand attachment) on customer loyalty. The full statistical results will further determine the strength and significance of these relationships. Conclusion and suggestion: The findings of this study indicate that customer loyalty in long-standing culinary businesses is significantly influenced by brand authenticity and perceived service value, both directly and through brand attachment.Business owners are encouraged to maintain brand consistency and deliver service experiences that create emotional and functional value to sustain long-term customer relationships.